Pengaruh Bahan Ajar Multimedia Interaktif Terhadap Hasil Belajar Peserta Didik Pada Pelajaran IPA: Sebuah Studi Meta-Analisis - Festiyed; Hermalina Daulay; Mila Ridhatullah (Postgraduate, University of Mataram, 2023)
Interactive multimedia teaching materials are teaching materials that combine two or more interactive media (audio, text, graphics, images, and video). Interactive multimedia is one of the teaching materials that can be used to support the learning process. The purpose of this study was to see how interactive multimedia influences students' mastery of concepts and cognitive learning outcomes in science learning. This type of research is meta-analysis research. The example used is 25 journals that meet the criteria. The data analysis technique is calculating the effect size of each journal, testing heterogeneity and testing hypotheses. Based on the results of data analysis in this study it can be concluded that in general interactive multimedia influences student learning outcomes. Specifically grouped into several moderator variables, it can be concluded that, first, interactive multimedia influences student learning outcomes, especially in physics and chemistry lessons. Second, interactive multimedia has an influence on the learning outcomes of class X and class XI students. Third, interactive multimedia has an influence on student learning outcomes when combined with cooperative learning models and inquiry learning.